Smoking Status and Outcomes following Lung Resection - Ahmed-Issap, Amber; Mantio, Kim; Jain, Shubham; Habib, Akolade; Brazier, Andrew; Raseta, Marko; Abah, Udo (The Thoracic and Cardiovascular Surgeon, 2023)
Background Surgical resection is the gold standard treatment for the management of early-stage lung cancer. Several modifiable factors may significantly influence postoperative morbidity and mortality. We examined the outcomes of patients following lung resection based upon preoperative smoking status to quantify the impact on postoperative outcomes.Methods Data from consecutive lung resections from January 1, 2012 to June 11, 2021 were included. Biopsies for interstitial lung disease and resections for emphysematous lung or bullae were excluded. Patients were divided into three cohorts: current smokers (those who smoked within 4 weeks of surgery), ex-smokers (those who stopped smoking prior to 4 weeks leading up to surgery), and nonsmokers (those who have never smoked). Patient's preoperative variables, postoperative complications, length of stay, and mortality were examined.Results A total of 2,426 patients were included in the study. A total of 502 patients (20.7%) were current smokers, 1,445 (59.6%) were ex-smokers and 479 patients (19.7%) nonsmokers. Of those smoking immediately prior to surgery 36.9% developed postoperative complications. Lower respiratory tract infections (18.1%) and prolonged air leak (17.1%), in particular, were significant higher in smokers. 90-day mortality (5.8%) was higher in the current smokers when compared with ex- and nonsmokers (5.3 and 1%, respectively). Median length of hospital stay, readmissions, and cost of hospital stay was also higher in the current smoker cohort.Conclusion Smoking immediately prior to surgery is associated with an increase in morbidity, mortality, and length of stay. Not only does this have a significant individual impact, but it is also associated with a significant financial burden to the National Health Service.
Keywords: lung cancer treatment (surgery; medical); outcomes (includes mortality; morbidity); nutrition; postoperative care